Observed influence of liquid cloud microphysical properties on ultraviolet surface radiation. Issue 5 (4th March 2014) - Mateos, D.; Pace, G.; Meloni, D.; Bilbao, J.; di, A.; de, A.; Casasanta, G.; Min, Q.
Abstract Measurements of different UV quantities (UV index, ozone photolysis rates, global and diffuse irradiances, and actinic flux spectra) and cloud properties were collected during a field campaign carried out in Southern Italy in May–June 2010. Independent measurements of cloud liquid water path and optical depth allowed retrieving the cloud effective radius. The cloud modification factor (CMF) is used to investigate the influence of liquid cloud properties on the UV radiation under overcast conditions. CMF was also simulated using a 1‐D radiative transfer model. Experimental and simulated CMF values for UV index (under overcast conditions) show a normalized root‐mean‐square error around 11%. Clouds with small effective radius determine a higher UV radiation attenuation than clouds formed by large particles. The CMFs for the UV index and the global spectral irradiance show a very weak dependence on the solar zenith angle (SZA), while the CMFs for actinic flux (both integrated and spectral) and diffuse spectral irradiance show a variation with SZA. The irradiance is more effectively attenuated at low SZA, while the actinic flux at high SZA. These effects are due to the different weight given to the direct and the diffuse components.